2000
DOI: 10.1063/1.481840
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally inelastic collisions of OH(X 2Π)+Ar. II. The effect of molecular orientation

Abstract: Orientation effects in inelastic collisions of OH(X 2Π)+Ar at an energy of 746 cm−1 have been studied in a crossed molecular beam experiment. The OH(X 2Π) radicals were prepared in the v=0, Ω=32, J=32, f state by hexapole state selection and oriented with their O-end or H-end towards the Ar atom by a static electric field in the collision zone. The orientation-dependent probability density function has been determined by laser induced fluorescence spectroscopy using a narrow band dye laser and the Stark mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 29 publications
1
58
0
Order By: Relevance
“…Collisions populating the F 1 (3/2e) level were most likely. Within the F 1 (5/2) level, collisions populating the lower Λ-doublet component of e parity were favored, consistent with findings of other 2 Π-rare gas systems (28,29 ). For the F 1 (3/2e) and the F 1 (5/2e/f ) levels, the transition probabilities were almost constant at higher collision energies.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Collisions populating the F 1 (3/2e) level were most likely. Within the F 1 (5/2) level, collisions populating the lower Λ-doublet component of e parity were favored, consistent with findings of other 2 Π-rare gas systems (28,29 ). For the F 1 (3/2e) and the F 1 (5/2e/f ) levels, the transition probabilities were almost constant at higher collision energies.…”
supporting
confidence: 74%
“…In a crossed beam set-up, rotationally inelastic scattering between state-selected OH radicals (X 2 Π 3/2 , v = 0, J = 3/2, f (27 ), referred to hereafter as F 1 (3/2f )) and Xe atoms is studied throughout the 0.14 to 1.14 kcal/mol (50 to 400 cm −1 ) region, with an overall energy resolution of ∼ 0.03 kcal/mol (13 cm −1 ). We chose the OH-rare gas system because, at higher collision energies, rotationally inelastic collisions have been studied for this system in great detail, both experimentally and theoretically; state-to-state cross-sections and the effects of molecular orientation have been determined (28,29 ). The energy range covered in the present study encompassed the energetic thresholds for inelastic scattering down to the lowest rotational levels of OH.…”
mentioning
confidence: 99%
“…Early calculations [17,18] on rotationally inelastic scattering of N 2 molecules with He atoms have shown that resonances occur at low collision energies, but the experimental verification of these predictions was not yet possible. Collisions of OH(X 2 Π) with rare gases have emerged as paradigms of scattering of an open-shell molecule with an atom [13,15,[19][20][21][22][23][24]. The OH-rare gas systems are good candidates for the observation and analysis of resonances in rotationally inelastic collisions because the collision energy can be reduced by Stark deceleration of the OH beam.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Steric asymmetries of the inelastic cross sections were measured by orienting the OH radicals with either the O-end or the H-end towards the Ar atom by a static electric field in the collision zone. 31 The collision induced reorientation of the OH radicals was measured by probing the Stark-split states of the products corresponding to different orientations. 32 Under thermal bulk conditions, the evolution of oriented or aligned OH (X 2 P) radicals was studied in collisions with argon by polarization spectroscopy.…”
Section: Introductionmentioning
confidence: 99%